Program Sosialisasi dan Pelatihan Kesiapsiagaan Kebakaran pada Kader Posyandu dan Masyarakat Desa Tunggulrejo, Kecamatan Jumantono, Karanganyar - Rici Riansyah; Jordan Syah Gustav; Nabila Putri 'Aisy Fauzia; Andrian Abib Abednego; Azka Nisa Nur Azizah; Dwita Nur Sabrina; Ilham Mustofa; Jannatika Finna Al Aufa; Naila Rizquna Maghriza; Rahsya Ariiqarlo Pahlavi; Theresia Nabila Pradita; Andrian Qymnastiar; Ezriani Ezriani; Rizqy Kartika Sari (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Mitigation is a series of efforts to reduce disaster risk, both through physical development and awareness and capacity building to deal with disaster threats. According to data from the Karanganyar District Disaster Management Agency (BPBD), fires are one of the most common disasters, especially in the Jumantono subdistrict. The lack of knowledge and awareness among villagers regarding fire management is a major threat. According to one community member, they have never received any socialization or training on fire disaster management. The Pos Pelayanan Terpadu or Posyandu is a basic health activity organized by, for, and with the community, especially for maternal and child health. Posyandu cadres are one of the driving forces in developing the knowledge of the Tunggulrejo Village community. The provision of socialization and training on fire preparedness for Posyandu cadres is a strategic step in instilling knowledge of fire emergency response in the community of Tunggulrejo Village. The results of the socialization that has been carried out show a significant increase in the knowledge and understanding of Posyandu cadres regarding the dangers, risks, and handling of fire disasters. Firefighting training using Traditional Fire Extinguishing Equipment (APAT) has become a provision for fire preparedness for Posyandu cadres.